Bioresponsive nanogels for protein delivery. Issue 1 (31st January 2022) - Xu, Xiao; Shen, Shiyang; Mo, Ran
Abstract: Protein drugs have attracted more attentions due to their high specificity and efficacy. However, the poor stability, plasma degradation, inferior cell membrane permeability, and immunogenicity severely limit the in vivo application of protein drugs. Nanogels are the nanosized crosslinked gels with high water‐loading capacities and large cavities for protein loading, which are able to increase the stability and decrease the immunogenicity for protein delivery. The bioresponsive nanogels possess the capability of programmatically releasing the protein drugs in an on‐demand manner at the target sites with distinct biosignals, which show considerable potential to increase the therapeutic efficacies and decrease the adverse effects of the protein drugs. In this review, we outline the recent advance in the bioresponsive nanogels for delivery of protein drugs, and survey the design of new materials and formulations that can respond typical biosignals, such as temperature, pH, reductive potential, and enzyme expression. The prospects and challenges are also discussed. Abstract : The bioresponsive nanogels show considerable potential to enhance the therapeutic efficacies and reduce the adverse effects of the protein drugs. This mini‐review summarizes recent advance in the applications of the bioresponsive nanogels for protein delivery and disease treatment.